MOTIVATION TO LEARN ENGLISH IN PRIMARY SCHOOL - Sam Hermansyah; Kok Shiong Pong (International Journal of Teaching and Learning, 2023)
In this work, the traits of children are illustrated, and this indicates the functions of primary school teachers. The focus of this study, which is the methods for inspiring kids to learn, is then reached. It is clear that the key to effective teaching and learning is student motivation. Motivation and pupils' success in learning English are positively correlated. Any successful teaching and learning strategy can be used to raise it in order to raise student achievement.